Psychometric properties of Gaudiebility Scale (Modulators of Enjoyment) for Children and Adolescents (GSCA). - Padrós-Blázquez, Ferran; Martinez-Medina, María Patricia; Guardia-Olmos, Joan; Graff-Guerrero, Ariel (Anales de Psicología / Annals of Psychology, 2021)
The decrease in the ability to enjoy can be considered a risk factor or marker of mental disorders. Therefore, it can be useful to have a scale to quantify gaudiebility in children and adolescents to develop strategies to improve gaudiebility. The objective of the present work was to build and analyze the psychometric properties of the Gaudiebility Scale for Children and Adolescents (GSCA). 1,264 primary, secondary and high school students responded to GSCA, Rosenberg’s self-esteem scale, Positive and Negative Affect schedule, Center of Epidemiological Studies of Depression scale. Through a confirmatory factor analysis using a robust maximum-likelihood estimation, an adequate adjustment was observed to 5 factors model (Enjoyment in Company, Self-efficacy versus boredom, Sense of humor, Imagination and Interest) related. In addition, an appropriate internal reliability (Cronbach α=0,794) was observed in the total scale and in the 5 subscales. Finally, an adequate concurrent and discriminant validities were observed. GSCA’s psychometric properties indicate appropriate internal reliability and validity. GSCA seems appropriate to quantify gaudiebility levels in children and adolescents.